2001
DOI: 10.1034/j.1600-0781.2001.017001002.x
|View full text |Cite
|
Sign up to set email alerts
|

Sunscreen protection in the ultraviolet A region: how to measure the effectiveness

Abstract: Products containing ultraviolet (UV) radiation absorbing or scattering ingredients provide varying degrees of protection from sunlight (or other UV sources), thus minimizing the deleterious effects on the skin. The ''sun protection factor'' (SPF) of sunscreen products has become a well recognized indicator of protection against sunburn induced predominantly by ultraviolet B radiation (UVB: 290-320 nm). A similar system of denoting sunscreen protection from ultraviolet A (UVA: 320-400 nm) radiation has not been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(52 citation statements)
references
References 29 publications
0
44
0
2
Order By: Relevance
“…Data from Central New Jersey have shown that in winter the UVA daily doses are only half that of a summer, spring or fall day. The UVB radiation changes more dramatically than the UVA radiation during the daytime as well as over the seasons as it is absorbed preferentially by the ozone in the stratosphere (longer path length during the winter and at low sun angles at the beginning and end of the day, resulting in lower UVB dose reaching the earth's surface) (Cole 2001).…”
Section: Environment-related Factors Affecting Uv-radiationmentioning
confidence: 99%
“…Data from Central New Jersey have shown that in winter the UVA daily doses are only half that of a summer, spring or fall day. The UVB radiation changes more dramatically than the UVA radiation during the daytime as well as over the seasons as it is absorbed preferentially by the ozone in the stratosphere (longer path length during the winter and at low sun angles at the beginning and end of the day, resulting in lower UVB dose reaching the earth's surface) (Cole 2001).…”
Section: Environment-related Factors Affecting Uv-radiationmentioning
confidence: 99%
“…Five products (Nos. 3,7,8,12,13) achieved the high category (3 stars). No products qualified for the ''highest'' category with the 4-stars rating.…”
Section: Resultsmentioning
confidence: 97%
“…This was the boundary used in this research to define the UVA waveband although the wavelength boundary between the UVB and UVA is defined at both 315 nm and 320 nm. The CIE [27] defines the boundary as 315 nm; however 320 nm is employed in a significant number of publications, due largely to the biological significance of wavelengths between 315 and 320 nm [28,29]. …”
Section: Dark Reactionmentioning
confidence: 99%